1989
DOI: 10.1111/j.1439-0442.1989.tb00782.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Plasma Fatty Acids, Prostaglandins and Antioxidant Balance in Bovine Mastitis

Abstract: Summary Plasma levels of free fatty acids (FFA) were measured in cows with mastitis. FFA levels are known to be elevated in milk of affected cows, and similar increases were now observed in blood plasma. Of the long‐chain polyunsaturated fatty acids which serve as precursors for prostaglandins (PGs), leukotrienes (LT) and related eicosanoids, arachidonic acid (C20: 4 ω−6) was elevated by 156 per cent and C20: 3 (consisting of both ω, −3 and ω −6) 153 per cent; eicosapentaenoic acid (20: 5 ω −3), not present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The variety of oxylipids expressed in both milk and plasma in this study represented some of the well-known enzymatic and nonenzymatic oxylipid biosynthetic pathways. Earlier studies on bovine coliform mastitis reported a few select prostanoids including PGE 2 , PGF 2α , and thromboxane B 2 in milk using immunoassay based detection techniques (Atroshi et al, 1989a). In the current study, the use of LC-MS/MS provided a more robust methodology to identify an expanded oxylipid network during acute bovine coliform mastitis.…”
Section: Discussionmentioning
confidence: 98%
“…The variety of oxylipids expressed in both milk and plasma in this study represented some of the well-known enzymatic and nonenzymatic oxylipid biosynthetic pathways. Earlier studies on bovine coliform mastitis reported a few select prostanoids including PGE 2 , PGF 2α , and thromboxane B 2 in milk using immunoassay based detection techniques (Atroshi et al, 1989a). In the current study, the use of LC-MS/MS provided a more robust methodology to identify an expanded oxylipid network during acute bovine coliform mastitis.…”
Section: Discussionmentioning
confidence: 98%
“…Generally, our study shows together with our earlier reports (Ali‐Vehmas et al., 1997; Malbe et al., 2003) that selenium may contribute to the protection of mammary gland from invading bacteria. Free radical generation and oxidative injury are thought to be important mechanisms contributing to morbidity, including mastitis (Atroshi et al., 1987, 1989, 2000). However, the mechanism by which the release of O 2 results in bactericidal effects is poorly understood, but is generally held to be related to the further generation of more reactive radical species, such as OH • , singlet oxygen and hypochlorite or hypothiocyanate (Del Maestro, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in dairy cows have shown that selenium deficiency is associated with nutritional muscular dystrophy, cystic ovaries, retained placental membranes, metritis and infertility (Jukola et al., 1996; Hemingway, 2003). Other studies have shown evidence that selenium deficiency is associated with increased prevalence to intramammary infections (Smith et al., 1984, 1997; Atroshi et al., 1987, 1989; Erskine et al., 1989, 1990; Malbe et al., 1995; Ryan, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…Oxygenation of arachidonic acid (cis C20:4n-6) through the cyclooxygenase (COX) and lipoxygenase (LOX) pathways, for example, produces several proinflammatory prostaglandins (PG), thromboxanes (TX), leukotrienes (LT), and hydroxyl derivatives such as hydroxyeicosatetraenoic acid (HETE). Increased expression of PGE 2 , PGF 2α , and TXB 2 derived from the COX2 pathway can be detected in the sera and tissues of cows during the pathogenesis of mastitis (Atroshi et al, 1989;Boutet et al, 2003). Alternatively, metabolism of n-3 FA including eicosapentaenoic acid (EPA, cis C20:5n-3) and docosahexaenoic acid (DHA, cis C22:6n-3) through the COX and LOX pathways leads to the production of proresolving eicosanoids called resolvins (RD) and protectins (PD; Serhan, 2009).…”
Section: Introductionmentioning
confidence: 99%